2016
DOI: 10.1080/19396368.2016.1246623
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with docosahexaenoic acid (DHA) improves seminal antioxidant status and decreases sperm DNA fragmentation

Abstract: The purpose of this study was to evaluate the effect of docosahexaenoic acid (DHA) dietary supplementation on semen quality, fatty acid composition, antioxidant capacity, and DNA fragmentation. In this randomized, double blind, placebo-controlled, parallel-group study, 74 subjects were recruited and randomly assigned to either the placebo group (n=32) or to the DHA group (n=42) to consume three 500-mg capsules of oil per day over 10 weeks. The placebo group received 1,500 mg/day of sunflower oil and the DHA gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 47 publications
(85 reference statements)
0
80
1
11
Order By: Relevance
“…In contrast, the addition of DHA and 20:5n3 (EPA) improved oxidative status in testicular tissue, measured as MDA‐TBARS. Dietary supplementation with DHA can improve total antioxidant capacity in seminal plasma (Martínez‐Soto et al., ). Several investigations have shown that DHA modulates the expression of genes encoding for different antioxidant proteins (Arab, Rossary, Flourie, Tourneur, & Steghens, ; Casañas‐Sánchez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the addition of DHA and 20:5n3 (EPA) improved oxidative status in testicular tissue, measured as MDA‐TBARS. Dietary supplementation with DHA can improve total antioxidant capacity in seminal plasma (Martínez‐Soto et al., ). Several investigations have shown that DHA modulates the expression of genes encoding for different antioxidant proteins (Arab, Rossary, Flourie, Tourneur, & Steghens, ; Casañas‐Sánchez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Safarinejad () found a significant increase in sperm concentration, total sperm count, motility, and normal morphology, and Martinez‐Soto et al . () discovered a reduction in sperm DNA fragmentation among men treated with omega‐3 capsules. Conquer et al .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were randomized controlled trials (RCTs), four studies were case–control trials, and eight studies were cross‐sectional. The RCTs investigated the effect of supplementation with omega‐3 FA on semen parameters in men with either a history of infertility (Conquer et al ., ; Safarinejad, ; Gonzalez‐Ravina et al ., ) or men undergoing evaluation for infertility (Martinez‐Soto et al ., ) (Table ). The observational studies examined whether there was an association between different dietary patterns, food groups or FA and fertility markers in semen (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations